FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMANDIRIAN PETERNAK MITRA DALAM USAHA AYAM BROILER DI KABUPATEN BANYUMAS - Zahidah, Khodijah; sugiarto, Mochamad; Wakhidati, Yusmi Nur (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Backgrund. This study aims to: 1) determine the characteristics of breeders consisting of age of breeders, breeder education, and length of breeding; 2) knowing the independence of partner breeders of broiler chickens; 3) knowing the relationship between farmer characteristics and the independence of partner breeders in the broiler chicken business in Banyumas Regency. Materials and Methods. The research target is broiler chicken breeders who participate in a partnership for at least one year and a total of forty respondents in the Banyumas Regency. The research was conducted using a survey method, with online media such as google form. Sampling was done using accidental sampling. The test was conducted using the Spearman rank correlation and descriptive analysis. Results. The average age of partner broiler breeders is 39.5 years. The average level of education of partner broiler breeders is 10,525 years, equivalent to education up to Junior High School. The average length of farming is 9.1 years. The average farmer's independence is a score of 37.9 and falls into the medium category. The results of the Spearman rank correlation analysis show that the education factor has a significant correlation with the level of independence while the age of the farmer and the length of breeding have no significant correlation. The solution given is that breeders should need additional education such as counseling to increase knowledge and start to increase independence in production.